Zakat sebagai Instrumen Pengentasan Kemiskinan dan Kesenjangan Pendapatan - Firmansyah (Jurnal Ekonomi dan Pembangunan, 2025)
Poverty and income inequality are still the major problems faced by Indonesia. Some scholars argue that economic development in the country had created a trade-off between economic growth and distribution. The conventional distribution approach seems to fail in overcoming these two problems. Hence, introduction of zakat mechanism is highly needed as an alternative approach to solve the problems. This paper aims to discuss role of zakat in reducing poverty and income inequality. The result shows that: First, there is a significant gap between potential and realization of zakat in Indonesia. Second, the official zakat institution has not played the important role in fundraising of zakat, because there are still many zakat payers which use the unofficial zakat institution. Third, the allocation of budget to support the productive zakat is still limited because of some obstacles faced. However, the presence of zakat programmes has reduced the poverty incidence and income inequality of zakat receivers.